Teaching business management from a perspective beyond self-interest (2012)
Profound reflection is currently being made in academic circles upon the principles which have long been the basis of economic theories in the teaching of business management. Amidst the issues discussed is the concept of human nature driven primarily by self-interest. Profit maximization and governance mechanisms in order to protect shareholders’ interests have become the essence of all good business practice. The present paper proposes a change in direction towards a wider and more realistic perspective with regards to the individual’s values within the sphere of the teaching of business management.